Metasurfaces: Three‐Dimensional Photoengraving of Monolithic, Multifaceted Metasurfaces (Adv. Mater. 1/2021). Issue 1 (4th January 2021) - Kang, Hong Suk; Jolly, Jason Christopher; Cho, Hyesung; Kalpattu, Abhishek; Zhang, Xu A.; Yang, Shu
Abstract : Metasurfaces are traditionally 2D metamaterials that manipulate light. In article number 2005454, Shu Yang and co‐workers bring them into 3D by photoengraving diverse metasurfaces onto different facets of monolithic, 3D microstructured arrays in a high‐throughput and on demand fashion. By patterning locally confined metasurfaces on a cube, each cube becomes a multiplexing pixel for color reflection and filtering.